Evidence Basis for Pharmacogenetic Testing in Psychiatry - Hays, Priya (Jour Med Resh and Health Sci, 2022)
Mental illness constitutes a healthcare crisis of enormous proportions, and affects millions worldwide, leading to clinical and economic affliction. Patients respond to antipsychotics, antidepressants, and mood stabilizers with varying response and outcomes, and differential de-grees of overall remission from schizophrenia, depression, and bipolar disorder. Pharmaco-genetic testing has increasingly been incorporated in clinical workflows to enhance drug response through dosing and mitigating of adverse drug reactions. The Food and Drug Administration (FDA) has issued a set of drug-gene pairs for other psychotropic drugs that affect the cytochrome P450 pathway, including CYP2D6, CYP2C19 and CYP2C9 and HLA-A/HLA-B gene variants, which when genotyped lead to phenotypic correlation to poor metabolizers (drug dosages need to be increased), ultrarapid metabolizers (drug dosages need to be decreased) and normal metabolizers (extensive or wild-type); (receive standard drug dosing), and affect responses to psychotropic medications. Based on clinical data, the analytic validity and clinical validity and clinical utility have been established to improve upon the “trial and error” process that psychiatrists frequently use to prescribe the right drug in the right dosage for their patients. This review discusses the evidence basis for utilization and implementation of pharmacogenetic data that lead to robust outcomes in patients suffering from mental illness, and the validation established by studies in this growing area of research. The recommendation is that psychiatrics utilize pharmacogenetic information for providing accurate information on responses to psychotropic and antidepressant medications in the diagnosis and treatment of their patients to mitigate the “trial-and-error” process.